PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA KELAS V PADA MATA PEMBELAJARAN IPAS DI SDN 1 KOTARAJA - Muhammad Sururuddin; Arif Rahman Hakim; Mijahamuddin Alwi; Firman Arizandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine whether the Project-Based Learning (PjBL) model can improve the critical thinking skills of fifth-grade students at SDN 1 Kotaraja and to identify the extent of its influence on their critical thinking skills in the Ilmu Pengetahuan Alam dan Sosial (IPAS) subject. IPAS, or Natural and Social Sciences, is a field of study that examines living and non-living things in the universe and explores human life as individuals and social beings interacting with their environment. IPAS learning provides students with opportunities to engage directly with their surroundings. This research employed a quantitative approach with a quasi-experimental design using a one-group pretest-posttest method. The research subjects consisted of 24 students. Data were collected through observation sheets, test instruments in the form of a series of questions, and worksheets designed to assess students’ critical thinking skills before and after the implementation of Project-Based Learning (PjBL). Data analysis was carried out using Descriptive Statistics, Normality Test, and Hypothesis Test (Paired Sample t-test). The results showed an increase in students’ pretest and posttest scores after applying the PjBL model. This was supported by the results of the paired sample t-test, which indicated a posttest score of -26.125 and a significance value of 0.000 (p < 0.05), meaning that there was a significant difference between the pretest and posttest scores.Based on these findings, it can be concluded that the Project-Based Learning (PjBL) model has a significant and positive effect on the critical thinking skills of fifth-grade students. This learning model can be used as an effective teaching strategy to encourage students to be more active in expressing their opinions.